2022
DOI: 10.1039/d2tc03400j
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of electronic bandgaps and subsequent implications on SQ efficiencies via strain engineering in ultrathin SnX (X = S, Se) nanowires

Abstract: First principles calculations have been undertaken to theoretically model ultrathin SnX (X = S, Se) nanowires (NWs). The formation energies for the ultrathin SnX NWs are negative and lower than...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 112 publications
0
2
0
Order By: Relevance
“…All of this intricate work must be conducted at extremely low temperatures and within a magnetic field that is 10,000 times stronger than Earth's field. 70 Ab initio calculations were applied to investigate ultrathin cubic NWs 71,72 and to find the critical thicknesses at which SnTe NWs go from a trivial insulating regime to a spin-orbit insulating phase and then to the TCI phase. 72 Great attention was recently dedicated to 2D pentagonal materials in different types of the Cairo pentagonal tessellation [73][74][75] and their topological properties.…”
Section: And Cubicmentioning
confidence: 99%
“…All of this intricate work must be conducted at extremely low temperatures and within a magnetic field that is 10,000 times stronger than Earth's field. 70 Ab initio calculations were applied to investigate ultrathin cubic NWs 71,72 and to find the critical thicknesses at which SnTe NWs go from a trivial insulating regime to a spin-orbit insulating phase and then to the TCI phase. 72 Great attention was recently dedicated to 2D pentagonal materials in different types of the Cairo pentagonal tessellation [73][74][75] and their topological properties.…”
Section: And Cubicmentioning
confidence: 99%
“…Theoretically, the SnTe NWs were investigated, and it was shown that different topological states can be realized under the application of various magnetic fields; 48 bulk Majorana modes are present when there is inversion symmetry, while under symmetry-breaking fields at the ends of the NWs, Majorana zero modes appear, while the Majorana bulk modes are gapped. 48 Ultrathin SnS and SnSe NWs were also studied by means of ab initio calculations, 49 while the NWs of trivial PbTe were also shown to be interesting for the possible presence of Majorana zero modes. 50,51 The 3D and 2D cases of these rock-salt chalcogenides are widely investigated from first principles, while the 1D structures like NWs are poorly investigated so far due to the huge number of atoms to be considered when we break the boundary conditions along 2 dimensions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Theoretically, the SnTe NWs were investigated, and it was shown that different topological states can be realized under the application of various magnetic fields; bulk Majorana modes are present when there is inversion symmetry, while under symmetry-breaking fields at the ends of the NWs, Majorana zero modes appear, while the Majorana bulk modes are gapped . Ultrathin SnS and SnSe NWs were also studied by means of ab initio calculations, while the NWs of trivial PbTe were also shown to be interesting for the possible presence of Majorana zero modes. , …”
Section: Introductionmentioning
confidence: 99%